Aplikasi Gipsum pada Kultivar Padi Tahan Salin - Syamsul Bahri; Adnan Amin; Fitriani Fitriani (Institut Pertanian Bogor, 2024)
Global climate change is predicted to increase the marginal land area, especially saline land, which affects the productivity of rice yields, so proper land management and tolerant varieties are needed. This study aimed to compare saline-tolerant cultivars and productivity at several concentrations of gypsum applications. The research was conducted on saline paddy soil in Cinta Raja Village, East Langsa District, Langsa City. We used fourteen cultivars studied, i.e., Batang Hari, Mendawak, Malaisia, Beres, Siak Raya, Martapura, Dendang, Air Tenggulan, Lambur, Banyuasin, Panasur, Impari, Indra Giri, and Margasari. The best results were found at the application of 1.5 tons per ha gypsum on the Dendang variety (G1V7) as shown by the higher plant height, i.e., 47.67, 60.53, and 71.20 cm at the ages of 30, 45, and 60 DAP, the number of tillers rice was 43.87 at 50 HST, and 39.87 at 60 DAP. The average weight of 1000-grains iwa 28.87 g, and an estimated yield was 7.63 tons ha-1. In conclusion, the Dendang variety, with the application of 1.5 tons of gypsum per ha, can be recommended for planting in saline soils. Keywords: gypsum, rice variety, salinity, sodium